Using diet-induced obesity to understand a metabolic subtype of osteoarthritis in rats. Issue 6 (June 2015) - Collins, K.H.; Reimer, R.A.; Seerattan, R.A.; Leonard, T.R.; Herzog, W.
Summary: Osteoarthritis (OA) in obese individuals is often attributed to joint loading. However, a subtype of OA, Metabolic OA, may be due to obesity-related intrinsic factors but remains to be evaluated experimentally against a known OA progression model. Objective: To evaluate if obesity contributes to OA onset using a high fat/high sucrose diet-induced obesity (DIO) model with anterior cruciate ligament-transected rats (ACL-X). Methods: Sprague Dawley rats ( n = 33) consumed high fat/high sucrose or chow diets for 12 weeks, were randomized to one of three groups: a unilateral ACL-X group, sham surgery group, or naïve non-surgical group. These animals were followed for an additional 16 weeks. At sacrifice, body composition, knee joint Modified Mankin scores, and 27 serum and synovial fluid cytokines and adipokines were measured. Results: Experimental limbs of obese ACL-X, obese Sham, and lean ACL-X animals had similar Modified Mankin scores that were greater than those obtained from lean Sham and naïve animals. Obese contralateral limbs had similar OA damage as ACL-X and Sham limbs of obese and ACL-X limbs of lean animals. Obese contralateral limb Modified Mankin scores had a strong correlation ( r = 0.75, P < 0.001) with body fat percentage. Serum leptin and synovial fluid IP10/CXCL10 best described Modified Mankin scores in contralateral limbs of obese animals. Conclusions: Mechanical factors produced OA damage in experimental limbs, as expected. Interestingly, OA damage in obese contralateral limbs was similar to mechanically perturbed limbs, suggesting that obesity may induce OA in a non-mechanical manner.